Efficient Encryption mechanism for financial transactions: Avoiding data loss and tackling collisions - et. al., Damanpreet Kaur, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Security in financial transactions is a necessity. This security is provided using various encryption mechanisms such as RSA, DES, AES, and hybrid encryption mechanisms. The problem, however, arises when financial transactions take place in the banking sector. This paper proposes a unique DNA-based block chaining to avoid any collision and to provide a high-end security during financial transactions. The block chaining mechanism provides a two-way security during financial transactions along with avoading data theft, as well as data loss, is avoided. The implementation results of the proposed system are presented in terms of throughput, encryption time, and decryption time. The results obtained for the encryption and throughput, are optimized using this approach, however, encryption time still requires certain modifications. The overall results are better than Changsong et al., 2020.